Quality of life in Parkinson’s disease patients: progression markers of mild to moderate stages - Raissa Carla Moreira; Marise Bueno Zonta; Ana Paula Serra de Araújo; Vera Lúcia Israel; Hélio A. G. Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To investigate which factors are associated with the quality of life decline in Parkinson’s disease patients from mild to moderate stages. Methods The Unified Parkinson’s Disease Rating Scale and Parkinson’s Disease Questionnaire-39 were used to evaluate clinical/functional data and the quality of life. Results The markers of clinical/functional worsening were drooling (p < 0.004), need for assistance with hygiene (p = 0.02), greater freezing frequency (p = 0.042), bradykinesia (p = 0.031), greater intensity of the resting tremor (p = 0.035) and “pill rolling” (p = 0.001). The decline in quality of life was related to stigma (p = 0.043), greater impairment in cognition (p = 0.002), mobility (p = 0.013) and for daily living activities (p = 0.05), and was considered more significant in men, married, older individuals, and those with a longer time of disease. Conclusions The quality of life worsening markers at the moderate stage were related to stigma, worsening of cognition, and to greater impairment in mobility and daily living activities.